Expression of the mRNA of the inflammatory component of the immune response in the period of the expected window of implantation in women with recurrent pregnancy loss in the programs of assisted reproductive technologies - К. П. Головатюк; В. Г. Дубініна; О. М. Носенко; Е. Т. Макшаєва; І. Л. Головатюк-Юзефпольська (Publishing House TRILIST, 2017)
The aim of study. To reveal the peculiarities of mRNA expression of the inflammatory component genes of the immune response in the expected window of the implantation in women with RPL in ART programs. Material and methods. 240 patients with RPL in ART programs and 100 conditionally healthy fertile women in the control group with the presence in history of at least one childbirth in time and the absence of episodes of miscarriage were examined. The average age of the examined women of the main group was 29.80 ± 0.30 years, the control group - 30.09 ± 0.32 (p >0.05). The average number of cases of involuntary termination of pregnancy after conduction of ART in main group was 3.24 ± 0.11, the average term of termination of pregnancy was 8.15 ± 0.65 weeks. All women had a paipel-biopsy of the endometrium during the expected implantation window. Samples were frozen at t = -70 °C. until the study. Reverse transcription -polymerase chain reaction was used to study mRNA expression of IL-1β, IL-2, IL-10, Foxp3, TLR9, IL-2Rα cytokine genes in endometrial biopsy obtained on the day of the implantation window. Results. It was found that the relative level of mRNA expression of IL-1β, IL-2, Foxp3, TLR9, IL-2Rα genes did not differ significantly in patients with RPL in the cycles of VRT and control group. A statistically significant decrease in mRNA expression of the IL-10 gene was noted. Conclusion. RPL in the treatment of infertile women in ART programs is associated with changes in the transcription profile of the endometrium during the intended implantation window and with a decrease in the expression level of the IL-10 gene mRNA.